How live-streaming commerce influences consumers’ impulse buying of near expiry-date food: implications for reducing food waste - Chuanhui Liao; Jia Luo; Siqi Wang; Yanxin Shen; Shuang Lin (Frontiers in Sustainable Food Systems)
Consumers often hesitate to purchase and consume food near expiry-date (FNED), contributing to significant food waste. The emerging practice of selling FNED through live streaming commerce (LSC) holds promise for promoting FNED sales and reducing food waste, as LSC can stimulate impulsive purchasing behavior among consumers. This study integrates the para-social theory, consumer value theory, and face negotiation theory to develop a research framework that examines how online interactions and face consciousness in Chinese culture influence consumers’ impulse buying of FNED through LSC. Using structural equation modeling and data from 352 valid online survey responses, the study reveals that streamer-viewer interaction (SVI) all contribute to impulse buying (IB). And perceived ease of use (PEOU), streamer-viewer interaction (SVI), and co-viewer interaction (CVI) strongly influence IB and is sequentially mediated by perceived risk (PR), highlighting the importance of PR. Only SVI directly impacts perceived value and further drives impulse buying. Additionally, the study demonstrates that face consciousness mitigates the impact of streamer-viewer interaction on impulse buying through consumers’ recognition of and reimbursements for streamers’ efforts. This study provides theoretical and managerial implications for online retailers and LSC platform practitioners for FNED sales.